The knowledge creation process in new product development teams in simulation games: a literature review - Feng, Yanan; Riedel, Johann Christian Karl Henry (Bertelsmann Verlag, 2014)
This paper describes some of the work that has been done to analyse the New Product Development (NPD) Simulation Game – COSIGA. The NPD process is one of knowledge creation – as the process progresses more knowledge is created by the NPD team members. To deepen the understanding of the knowledge creation process with the Cosiga game a literature review of knowledge creation in NPD was undertaken. The journals covered by the review were the top management journals. The literature review showed that the existing knowledge creation theories and models do not provide sufficient explanation as to how individuals in a multi-disciplinary team environment create knowledge, or what type of developmental stages team interaction goes through to develop new products. This paper describes the results of a literature review on knowledge creation in new product development and of relevant empirical studies. The paper outlines the starting point for how to analyse interactions in team-based processes, whether simulations like Cosiga, or in practice.